THE EFFECTIVENESS OF ISLAMIC PREMARRIAGE COUNSELING TO READINESS FOR HOUSEHOLD LIFE - Irman Irman; Silvianetri Silvianetri; Zubaidah Zubaidah; Putri Yeni; Wahyu Gusria; Hanifah Usman; Risvan Siraj (Alfuad: Jurnal Sosial Keagamaan, 2021)
The dominant problem experienced by prospective brides who will marry is the low level of readiness to enter married life, if neglected, this condition will have an impact on satisfaction after marriage. This study aims to examine the effectiveness of Islamic premarital counseling on increasing married life readiness. The research method used is experimental, especially the one group pretest and posttest design. The research population is prospective brides who have been registered at the Tanah Datar Regency Religious Affairs Office. The research sample was 8 people with the criteria indicated that the level of readiness for married life was low. Data were collected using a household readiness scale, with data analysis using the paired samples t test through the SPSS computer program. release 20. The results of the study found that Islamic premarital counseling is effective in increasing the readiness of married life of the prospective bride and groom. The increase occurred in every dimension of readiness for married life, namely mental, spiritual, social and financial readiness.